Avaliação de habilidades de prontidão mediante o inventário de capacidades primarias de valett e nível de desempenho em leitura - Viessi, Vani Ruiz; Zamberlan, Maria Aparecida Trevisan (Semina: Ciências Agrárias, 1980)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The aim of this study was verify if three variables-criteria were correlated to reading achievement: The Valett Inventory of Primary Skills, scores in reading labeled by teachers and performance by pupils in a dictation of words. The subjects were twelve children, enrolled Public Schools in Londrina, whose average age is 7 years and 8 months old, coming from urban middle class, one half instructed by a phonetic method and one half by a sight word method. The material consisted of Valett Inventory of Primary Skills, pupils score's bulletins and card Word to dictation. The results which were found by Mann Whitney U Test showed a statistic significant difference between performance in Valett Inventory of Primary Skills x Dictation of words for the group instructed by sight - work method. Bye the statistic method of correlation by rank with correction factor (Spearman) among the three variables-criteria, only a statistic significant correlation was found for: Valett x Dictation of words (Critérium II) in the group instructed by sight-word method